2018
DOI: 10.1097/jtn.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Changes in Quality of Life in Trauma Patients: A Focus Group Study

Abstract: Quality of life (QoL) following a physical trauma is still insufficiently known from a patient perspective. The aim of this study was to qualitatively report perceived changes in QoL after trauma. Focus groups were conducted. Patients admitted to the hospital were eligible for inclusion if they had a lower extremity trauma, severe injuries, or severe traumatic brain injury (TBI). Patients 75 years or older were invited. To analyze the perceived changes in QoL, open coding was used. Patients (n = 20, M = 55 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Individuals with TBI also utilized psychological coping strategies that helped them manage emotional distress and promote balanced thinking. These strategies included adopting a present moment focus and cultivating mindful awareness of daily activities (Douglas, 2013; Kruithof et al, 2018), as well as a number of strategies to promote positive mood (e.g., cultivating gratitude and optimism) (Mumbower et al, 2019; Nalder et al, 2013) and a positive framing of their current challenges and identity (e.g., focusing on values, cultivating acceptance, adopting a growth mindset) (McPherson et al, 2018; Salas et al, 2018). For example, participants described viewing the TBI as a “new beginning” linked to a renewed desire to pursue goals as well as a chance to modify their health behaviors (e.g., sleep, exercise, substance use) to optimize recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with TBI also utilized psychological coping strategies that helped them manage emotional distress and promote balanced thinking. These strategies included adopting a present moment focus and cultivating mindful awareness of daily activities (Douglas, 2013; Kruithof et al, 2018), as well as a number of strategies to promote positive mood (e.g., cultivating gratitude and optimism) (Mumbower et al, 2019; Nalder et al, 2013) and a positive framing of their current challenges and identity (e.g., focusing on values, cultivating acceptance, adopting a growth mindset) (McPherson et al, 2018; Salas et al, 2018). For example, participants described viewing the TBI as a “new beginning” linked to a renewed desire to pursue goals as well as a chance to modify their health behaviors (e.g., sleep, exercise, substance use) to optimize recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that patients' coping abilities and recovery expectations will influence their prognosis [11,15,38]. Busse et al [38] showed that a worse coping and pessimism regarding recovery 6 weeks after surgical repair of open extremity fractures was predictive to persistent pain, reduced quality of life, and pain interference after 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that individual recovery expectations influenced the recovery after trauma or orthopedic surgery [11,12]. Patients with higher baseline expectations for a total hip or knee replacement showed greater improvements in 1 year [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In older age groups, it is one of the most important causes of death, behind cardiovascular disease and cancer (GBD 2017 Mortality Collaborators, 2018; Nickson, 2015). In addition, trauma negatively influences a patient's physical functioning and health‐related quality of life (HR‐QOL; Kendrick et al., 2011; Kruithof et al., 2018; van der Sluis, Eisma, Groothoff, & ten Duis, 1998; Stalp et al., 2002). Since trauma patients are typically relatively young, the associated loss of disability‐adjusted life years (DALYs) is higher than in any other disease (Murray et al., 2012).…”
Section: Introductionmentioning
confidence: 99%